Leaping at shadows / Megan Atwood - Atwood, Megan
Madeline, a new student at the Quincy dance school, sneaks out after curfew with a group of other girls and discovers a network of hidden passages underneath the building. A series of disturbing coincidences begins to follow the girls afterward, and Madeline suspects that the school may be haunted